Time in the administrative dispute : test of comparative and analysis of the french rights and the states of french-speaking Africa - (:unkn) unknown (My University, 2016)
In the administrative lawsuit, time must reconcile the rights of justiciable and the principle of legal security. The comparative analysis of the French rights and the French-speaking country of Africa, following the example of Cameroon and of Gabon, gives the opportunity to observe the various facets of the time seized by the right in administrative dispute. In France, indeed, the temporal framework of the lawsuit is not exclusively defined by the legislator, it is also the work of jurisprudence and even of justiciable, on the one hand, and, on the other hand, this time is identified according to an approach at the same time quantitative, qualitative and of the economic situation. Thus, in theory, in the French administrative dispute, time appears in a flexible or malleable form. In the African rights, on the other hand, the temporal framework of the administrative lawsuit is more regulated, i.e. a time prescribes in advance by the texts, which is expressed with the requirement, on the one hand, and, on the other hand, one even observes a primarily quantitative approach from the point of view of his determination. Under these conditions, it appears, in theory, like a rigid time, a solidified time, contrary to a time chosen as it is the case in French right. This dynamic, or flexible approach, of time observed in French right is, in spite of the risk of extension of the time of the procedures which it can cause, advantageous with the justiciable ones. It is undoubtedly the reflection of a French administrative law which evolved to the protection of the citizens, contrary to the rigid form of time, observed in the African legislations which, making the good share with the principle of legal security to the detriment of the rights of justiciable, is the expression of an administrative law primarily turned towards the effectiveness of the administrative action.
Keywords: African Research